1997
DOI: 10.3109/08880019709028778
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Meningitis Following a Thrombotic Microangiopathy in an Unrelated Donor Bone Marrow Transplant Recipient

Abstract: In patients undergoing bone marrow transplantation cryptococcosis is rarely encountered. We report a fatal case of Cryptococcus meningitis in a 12-year-old girl with acute lymphoblastic leukemia (ALL) in second remission who had a transplant from a human leukocyte antigen (HLA)-identical unrelated bone marrow donor. The conditioning regimen was thiotepa, cyclophosphamide, and total body irradiation (TBI); graft-versus-host disease (GVHD) prophylaxis consisted of cyclosporin A, methotrexate, and antilymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Furthermore, nonbacterial agents, such as herpes virus [27,28], HIV [20] or other viruses [29] and fungal agents [30], have also been associated with TMA. The association between acute infection and TMA could either be related or not to an increase of susceptibility to infective agents or may be triggered by the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, nonbacterial agents, such as herpes virus [27,28], HIV [20] or other viruses [29] and fungal agents [30], have also been associated with TMA. The association between acute infection and TMA could either be related or not to an increase of susceptibility to infective agents or may be triggered by the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Furlan and Tsa茂 [14,15] have independently reported that TTP patients have a deficiency of von Willebrand factor-cleaving protease activity, either congenital or acquired, related to an inhibitory IgG autoantibody. Many case reports have described various infectious agents as responsible for inducing TMA, such as intra-or extra-cellular bacterial agents, viruses and fungal agents [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Recognition of these underlying diseases appears to be important in the management of TMA since they may be responsible for relapses or even treatment failure, and thus should be intensively diagnosed and treated [31].…”
Section: Organ Dysfunctionmentioning
confidence: 99%
“…In our study, CCD mice with an absolute blockade in T cell restricted Notch signaling were unable to control fungal burden in the lungs and prevent later fungal dissemination to the CNS, which is the major cause of morbidity and mortality in human cryptococcal disease. Many patients likely to receive Notch-targeting therapies are already at risk of cryptococcosis; C. neoformans is the third most common fungal infection in organ transplant recipients (3) and has been reported in bone marrow transplant patients undergoing prophylaxis for GVHD (78). Thus, our results highlight the importance of developing short term therapies targeting Notch signaling to prevent cryptococcal infections; as prolonged and pan-Notch inhibition could put patients at even greater risk for disseminated cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although morbidity and mortality are relatively high among neonates and children with fungal infections, there are very few published data to characterise toxicity among neonates [1,7]. Three groups of children are particularly susceptible to fungal infection: low birthweight premature neonates with prolonged hospitalisation [1][2][3]; children with a suppressed immune defence system [4,10]; and those undergoing organ or bone marrow transplantation [5,6]. Within these groups of neonates and children, the pharmacokinetics of 5-FC may be unpredictable [1].…”
Section: Introductionmentioning
confidence: 99%
“…There is a relatively high rate of mortality in up to 25-50% of cases of fungal infection [1][2][3] among children with suppressed immune defences, including cryptococcosis in human immunodeficiency virus (HIV)-infected children [4] and those who are undergoing organ or bone marrow transplantation [5,6].…”
Section: Introductionmentioning
confidence: 99%